Assessing Online Flow Across Cultures: A Two-Fold Measurement Invariance Study - Hu, Elwin; Stavropoulos, Vasileios; Anderson, Alastair; Clarke, Michael; Beard, Charlotte; Papapetrou, Stelios; Gomez, Rapson (Frontiers in Psychology, 2019)
The association between online Flow and Internet Gaming Disorder (IGD) has attracted significant attention. Despite the consensus that online Flow plays a pivotal role in the development of IGD and other Internet addictive behaviours, there has been a lack of consistency in measurement scales used to assess online Flow. Even widely used measures of online Flow have not been psychometrically assessed across culturally diverse populations of gamers. Such an assessment would enhance the accuracy of cross-cultural comparisons regarding the association between online Flow and IGD. Attending to this need, the present study assessed the psychometric properties of the binary coded (i.e. Yes, No) Online Flow Questionnaire (OFQ), while concurrently taking into consideration country, age, language, and mode of data collection (online or face-to-face) differences. Two sequences of successive multiple group confirmatory factor analyses were used to assess the psychometric properties of the OFQ, between: a) emergent adults from the United States of America (N = 482, Mage = 25.23, SD = 2.746) and Australia (N = 168, Mage = 23.55, SD = 3.37) and b) adolescents from Greece (N = 1579, Mage = 16.12, SD = .849) and Cyprus (N = 1372, Mage = 15.54, SD = .656). Configural and partial metric invariance were confirmed between the USA and Australian samples. For the Greek and Cypriot samples, results indicated full configural and metric invariance. These results provide initial information to researchers and clinicians of the extent to which the OFQ maintains its consistency when used across cultures and invite for further cross-cultural studies in the field. Implications, as well as limitations, are discussed.